Do asset purchase programmes shape industry dynamics? Evidence from the ECB's SMP on plant entries and exits - Manfred Antoni; Talina Sondershaus (Halle Institute for Economic Research (IWH), 2021)
Asset purchase programmes (APPs) may insulate banks from having to terminate relationships with unproductive customers. Using administrative plant and bank data, we test whether APPs impinge on industry dynamics in terms of plant entry and exit. Plants in Germany connected to banks with access to an APP are approximately 20% less likely to exit. In particular, unproductive plants connected to weak banks with APP access are less likely to close. Aggregate entry and exit rates in regional markets with high APP exposures are also lower. Thus, APPs seem to subdue Schumpeterian cleansing mechanisms, which may hamper factor reallocation and aggregate productivity growth.
Keywords: E58; G21; G28; G33; 330; plant exit; factor reallocation; asset purchase programmes